Petal stomata of Hemerocallis citrina Baroni are sensitive to abscisic acid - Gong, Lei; Hua, Ye; Su, Yun-Yun; Zhang, Bo; Yao, Li-Ting; Alharbi, Basmah M.; Hasan, Md. Mahadi (Frontiers in Plant Science, 2025)
In response to drought stress, abscisic acid (ABA) plays a crucial role in regulating stomatal closure in both leaf and floral tissues. Studies on stomatal regulation have primarily focused on the leaves of vascular plants, but stomatal regulation of flowers remains underexplored. The current study was conducted on the petals of ‘Ma Lin’ daylily (Hemerocallis citrina Baroni) to assess the morphological characteristics of petal stomata, stomatal aperture, gas exchange, and the mechanisms of ABA signaling in response to treatments with ABA-related chemicals and their corresponding scavengers. The study showed that stomata are primarily located in the lower epidermis of the petals, arranged in a strip near the central vein, and exhibit relatively low density; the guard cells contain a large number of chloroplasts. Exogenous ABA induced stomatal closure in the petal stomata, and the gas exchange assay indicated that stomatal conductance decreased when exogenous ABA was introduced into the transpiration stream. The stomatal aperture assay revealed a 32.78% decrease following a 10 µM ABA treatment. Furthermore, both hydrogen peroxide (H2O2) and nitric oxide (NO) were involved in the ABA-induced stomatal closure process, with H2O2 acting as an upstream component of NO. Overall, these results suggest that physiologically active stomatal control is present in the flower of ‘Ma Lin’ daylily under drought stress, consistent with the regulation observed in leaf stomata.